Fun with Fabric - Bawden, Juliet (London Hamlyn Children's Book, 1993)
This title in the "Creative Crafts" series is an illustrated activity book packed with ideas for original projects with fabrics. It includes an introduction to skills and techniques; step-by-step instructions; and photographs of finished projects.
Include Color Illustrations
Keywords: Textile crafts -- Textile painting -- Handicraft